Smear Layer Removal from the Apical Third Using the Er,Cr:YSGG Photon-induced Photoacoustic Streaming - Rasheed , Sabreen Sabah; Jawad, Hussien Ali (Iranian Endodontic Journal, 2021)
Introduction: The purpose was to study the influence of Erbium,Chromium:Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) laser at short pulse duration on smear layer removal from apical root third. Materials and Methods: Twenty-four single-rooted mandibular premolars were used. The roots length was cut to 14 mm and instrumented using the Protaper Gold system to size 40/0.06. The samples were divided into four groups (n=6) as follows: (A) conventional irrigation with 5 mL of 17% Ethylenediaminetetraacetic acid ( EDTA), (B) passive ultrasonic irrigation with 5mL of 17% EDTA, (C) Er,Cr:YSGG induced photoacoustic streaming (PIPS) with 5 mL of 17% EDTA and (D)Er,Cr: YSGG induced PIPS with 5 mL of 5.25% sodium hypochlorite (NaOCl). After final irrigation with normal saline and drying, the roots were painted with nail varnish externally, and 2%methylene blue dye was injected into the canal. The tooth split horizontally at the fourth millimetres. The picture was taken by a professional Digital SLR camera. The dye penetration was measured using analytical software (measure picture CAD-KAS Kessler Germany). Dunnett’s test was used to compare control group against experimental groups. Results: After the statistical test, the highest mean percentage was presented in the laser group with 17% EDTA (Group C=85.9804) followed by the laser group with 5.25% NaOCl (Group D=69.7817) and ultrasonic group (Group B=34.5453) respectively and the lowest mean percentage was in the control group (Group A=20.7969). Conclusion: Based on this in vitro study, PIPS technique using Er,Cr:YSGG pulse laser (0.5 W,5 Hz, air and water off) at short pulse duration and 17% EDTA proved effectively in smear layer removal, while the PIPS proved an acceptable result when the laser is used alone assisted by NaOCl.